(untitled) (Al-Academy, 2025)
Digital simulation techniques in the field of designing and analysing woven fabrics is a recent technological revolution that allows researchers and engineers to create more efficient and accurate models and analyse the mechanical and physical properties of textiles before starting manufacturing, which saves time and effort compared to traditional methods. The research aims to evaluate the accuracy and efficiency of TexGen in simulating woven fabrics, and identify the challenges and limitations associated with using TexGen. The study found that TexGen digital simulation software is able to represent textile structures with high accuracy, but is dependent on design settings and the quality of input data, and is an alternative to the traditional method, reducing cost and time and facilitating the optimisation of fabric design before manufacturing. The research recommended the following: Improved integration of TexGen with advanced numerical simulation software to provide more comprehensive analysis. Conduct comparative studies with other types of simulation and numerical modelling techniques to better identify advantages and disadvantages.